Titanium Carbide Nanoparticle‐Decorated Electrode Enables Significant Enhancement in Performance of All‐Vanadium Redox Flow Batteries. Issue 8 (25th April 2016) - Wei, Lei; Zhao, Tianshou; Zeng, Lin; Zhou, Xuelong; Zeng, Yikai
Abstract: In this work, we demonstrate that titanium carbide (TiC) nanoparticles exhibit high catalytic activity for the redox reaction of V 3+ /V 2+ in acid solution. TiC nanoparticles enable the oxidation peak potential to be negatively shifted by 100 and 183 mV relative to that of pure carbon nanoparticles and that of pristine carbon paper, respectively. A TiC nanoparticle decorated carbon paper electrode is prepared and used as the negative side of a single vanadium redox flow battery. The battery demonstrates an energy efficiency of 80.7 % at a high current density of 100 mA cm −2 ; this value is 12.3 % higher than that of the battery with the pristine electrode. The findings presented in this work suggest that titanium carbide nanoparticle decorated carbon paper exhibits great promise as a high‐performance electrode for vanadium redox flow batteries. Abstract : What a performance ! The improved performance of a vanadium redox flow battery is attributed to the use of a TiC‐decorated carbon paper electrode (TiC/CP). TiC nanoparticles show a powerful catalytic effect towards the V 3+ /V 2+ redox reaction. Moreover, the proposed electrode maintains its chemical and mechanical stability in the acid environment of the flowing electrolyte.